The Impact of the “Semente” Program on the Family-Focused Practice of Mental Health Professionals in Portugal - van Doesum, Karin; Maia, Teresa; Pereira, Catarina; Loureiro, Monica; Marau, Joana; Toscano, Lurdes; Lauritzen, Camilla; Reedtz, Charlotte (Frontiers in Psychiatry, 2019)
Background: Children of parents with mental illness (COPMI) are a high-risk group. There is a strong association between parents’ psychiatric disorders and the incidence of psychopathology in their children. These children need to be identified and supported by mental health workers early, and hence clinical practice in adult mental health services needs to change from a focus on individual patients to systemic family focus. ‘Semente’, a mental health promotion program developed by the Psychiatry Service of Fernando Fonseca hospital (Lisbon, Portugal), had been established to identify these children and families and promote their mental health – by decreasing the impact of risk factors and promoting protective factors. The program included preventive COPMI interventions and implementation of activities offered to families with children in the mental health care. The aim of the present study was to evaluate changes in mental health care after the training in ‘Child Talks’ intervention (2 to 3 psycho-educational meetings with parents and children) and implementation of the ‘Semente’ program. Methods: Participants (N=51) were all professionals from Psychiatric Service of Fernando Fonseca Hospital who received Child Talks training. The Family-Focused Mental Health Practice Questionnaire (FFMPQ) was used to measure change in professionals’ attitudes, knowledge, confidence and organizational structure in working with these families. All participants filled in the questionnaire before training, and 10 months later. Results: The results showed that, from pre to post measurement, the professionals changed clinical practice significantly. The largest changes were visible in the improved provision of support at the workplace for family focused practice and the clarity and availability of the policies and procedures. Furthermore, the skill and knowledge of the mental health workers showed significant improvement at posttest. Conclusion: The positive results of this study were not unexpected; the training, implementation of routines and procedures as well as workplace support were aims of the ‘Semente’program. Interpretation of the results should be taken with caution because of the small sample and the lower reliability of some of scales of the FFMPQ. The results indicate that professionals moved from a patient focus to a family focus during the implementation of the ‘Semente ’program.